LEARNING STYLE FOR MASTERY ACCORDING TO COGNITIVE STYLE (INDEPENDENCE VS. DEPENDENCE ON COGNITIVE FIELD) AND ITS IMPACT ON LEARNING DISCUS THROWING EFFECTIVENESS FOR STUDENTS - Jasim Mohammed, Riyadh (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2024)
The research problem focused on the weakness of learners in performing the discus throwing activity, which students should learn and master appropriately for each skill before moving on to the next one. The inability to master these skills is attributed to deficiencies in the learning process that limit the learners' skill acquisition, the lack of sufficient time to address issues that may arise during the learning process, or shortcomings in the adopted learning style. Therefore, the researcher decided to study this problem by using a mastery learning style to achieve the best results and bring learners to a certain level of performance, enabling them to move to the next skill. Classifying students based on the independence versus dependence on the cognitive field scale, creating an educational curriculum that teaches students how to throw discuses independently versus dependently on the cognitive field, and assessing the efficacy of the curriculum. For the academic year 2023–2024, the researcher used an experimental strategy that was appropriate for the nature of the problem. The study involved 42 fourth-year students from the University of Kufa's College of Physical Education and Sports Science. Pre-tests, the use of the curriculum, post-tests, statistical techniques, findings, and their discussion were all included in the primary experiment. Based on the findings, the researcher deduced that the students could be classified as independents or dependents on the cognitive field using the independence versus dependence scale, and that teaching the sample students discus throwing through the mastery learning style was a beneficial use of the educational curriculum, and that the educational curriculum using the mastery learning style had a greater impact on the group of independents than on the group of dependents on the cognitive field, based on the conclusions drawn by the researcher.